Spatial Analysis of Healthcare Facilities in Mersam Subdistrict - Susana, Neti; Ulni, Arie Zella Putra; Zuriyani, Elvi (Universitas Lampung, 2024)
This study aims to assess and analyze healthcare facilities in the Mersam Subdistrict. The research employs a descriptive quantitative approach, utilizing a regional study design with a spatial analysis based on Geographic Information System (GIS) software. The author seeks to understand the distribution, accessibility, and performance of these healthcare facilities. The Mersam Subdistrict serves as the population unit for this research. The findings reveal that the distribution of healthcare facilities in the Mersam Subdistrict includes community health centers (Puskesmas), assistant community health centers (Puskesmas Pembantu), and village health posts (Poskesdes). Accessibility to these healthcare facilities is defined as 3,000 meters for Puskesmas, 1,500 meters for Puskesmas Pembantu, and 1,000 meters for Poskesdes. These radii are established based on the Indonesian National Standards (SNI) 03-1733-2004 regarding the planning of urban residential environments. The analysis indicates that the facilities can be accessed effectively by the community. Performance assessments of the healthcare facilities in Mersam, derived from questionnaire surveys, reveal mixed levels of satisfaction among the public. For the Puskesmas, the satisfaction survey indicates positive feedback for Mersam Puskesmas. Among the assistant community health centers, Mersam Pustu received satisfactory ratings, while Belanti Jaya Pustu received a rating of dissatisfaction. The village health posts (Poskesdes) predominantly indicated a level of dissatisfaction among users.Keywords: Distribution; Affordability; Performance of Health Facilities